2017
DOI: 10.31138/mjr.28.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Can rheumatologists diagnose and manage Giant Cell Arteritis better than nonrheumatologists? The Maltese Experience

Abstract: OBJECTIVES: Giant Cell Arteritis (GCA) remains a challenge both in terms of diagnosis and management as patients may present to several different specialists. The objectives were to determine incidence of biopsy-proven GCA in Malta and to compare the management between rheumatologists and nonrheumatologists. METHODS: This was a retrospective observational population study of patients with suspected GCA who underwent a temporal artery biopsy (TAB) between 2012 and 2015. Data collected consisted of demographics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…However, only 12% of rheumatologist referrals in our study resulted in a positive TAB. While other studies have shown rheumatologists to have a higher positivity rate when requesting TAB compared with nonrheumatologists, 22 this was not the case in our study.…”
Section: Rheumatology Made Most Referrals For Tabcontrasting
confidence: 97%
“…However, only 12% of rheumatologist referrals in our study resulted in a positive TAB. While other studies have shown rheumatologists to have a higher positivity rate when requesting TAB compared with nonrheumatologists, 22 this was not the case in our study.…”
Section: Rheumatology Made Most Referrals For Tabcontrasting
confidence: 97%
“…This could be due to differing referral patterns of GCA patients at different centers. Cefai et al 27 found that 31% of TABs requested by rheumatologists were positive, whereas only 14% of TABs requested by other physicians were positive. A center where rheumatologists are the predominant referring physician could have a higher positivity percentage, as this specialty is historically more accurate at requesting TABs that go on to be positive.…”
Section: Discussionmentioning
confidence: 99%
“…In a commentary, Cefai at al. 6 asked the question whether rheumatologists or non-rheumatologists in Malta fare better in diagnosing and managing giant cell arteritis. They showed that temporal artery biopsy (TAB) requested by rheumatologists was more likely to be positive than TAB requested by non-rheumatologists, but the percentage was low (30% vs 14%).…”
mentioning
confidence: 99%